P643 Effectiveness of enhanced recovery after surgery in IBD: a propensity score matched cohort study in a single Italian centre. (25th January 2019) - Mineccia, M; Daperno, M; Massucco, P; Menonna, F; Gentile, V; Germani, P; Mendolaro, M; Rocca, R; Ferrero, A
Abstract: Background: Enhanced recovery after surgery (ERAS) provides many benefits for patients with colorectal cancer. However, its application to patients with Crohn's disease (CD) is still questioned because of lack of evidence. The aim of this propensity-matched study was to validate the results of ERAS protocol on CD patients. Methods: A retrospective analysis of patients undergoing ileo-colic resection for primary or recurrent CD from 2007 to 2017 was carried out. Patients enrolled in ERAS protocol were compared with those undergoing standard care. Patients were propensity matched into two equal groups (ERAS vs. non-ERAS) according to stardard propensity score procedures. Propensity match was carried out considering the variables affecting length of stay. Patient demographic characteristics, length of hospital stay, bowel function, oral intake, and perioperative morbidity were analysed. Results: In the study period, 23 (11%) out of 215 patients were selected for analysis as ERAS group. When unmatched groups were compared, significant differences were noted for gender, mean American Society of Anesthesiologists score, mean operative time. Median length of stay in ERAS and non-ERAS groups was 6 and 9 days ( p = 0.002), respectively. Early bowel movement (within 3 days) in ERAS and non-ERAS groups was 14 (61%) and 3 (13%, p < 0.001), respectively. Variables used for propensity match are listed in Table 1. Patients who tolerated early solid oral intake (within 3 days) in ERAS and non-ERAS groups were 18 (78%) and none respectively ( p < 0.001). However, after propensity match, no significant difference in postoperative outcomes were shown between the two groups, comparing ERAS and non-ERAS subgroups (Table 2). Conclusions: This propensity score matched study showed a significantly shorter hospital stay, earlier stool movement and return to free oral intake for patients with primary or relapse ileo-colic CD undergoing laparoscopic or open surgery, enrolled in ERAS protocol. It validates the ERAS protocol for a subgroup of complex pathology such CD and shows that optimised perioperative care combined with experienced surgical team may lead to further improvements in surgical outcomes for CD patients